Nano-hollow particles and method for producing nano-hollow particles

The method for producing nano-hollow particles with frame-shaped silica shells, using organic acid-coated calcium carbonate and sol-gel reaction, addresses the complexity and uniformity issues in existing methods, achieving efficient and uniform adsorption without additives.

JP2025044320APending Publication Date: 2025-04-02NAT UNIV CORP TOKAI NAT HIGHER EDUCATION & RES SYST +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023151823
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

Existing methods for producing nano-hollow particles with specific adsorption properties are complex and require the use of additives or surfactants, which can affect the uniformity and efficiency of adsorption.

Method used

A method for producing nano-hollow particles with frame-shaped silica shells using organic acid-coated calcium carbonate particles, where silicon alkoxide and a base catalyst are mixed to form a silica shell by sol-gel reaction, and calcium carbonate is dissolved with acid, all without using additives or surface modifiers.

Benefits of technology

This method allows for the production of mesoporous nano-hollow particles with high surface uniformity, enabling efficient and uniform adsorption of specific substances, and simplifies the process by eliminating the need for additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044320000001_ABST
    Figure 2025044320000001_ABST
Patent Text Reader

Abstract

To provide nano-hollow particles composed of a frame-shaped silica shell and a method for producing the same.SOLUTION: A method for producing nano-hollow particles comprises: a dispersion step in which organic acid-coated calcium carbonate particles obtained by coating the surface of calcium carbonate particles with an organic acid are dispersed in an organic solvent; a shell-forming step in which a silicon alkoxide and a base catalyst are mixed in the dispersion liquid to form a silica shell by a sol-gel reaction; and an acid treatment step in which the calcium carbonate is dissolved by an acid, and the method does not use surfactants or surface-modifying agents as additives. Nano-hollow particles have an outer diameter of 30 nm to 300 nm and are composed of a silica shell that is a spherical, ellipsoidal, cylindrical, or entirely six-faced frame-shaped, the silica shell having one or more communication holes for communicating the inner hollow with the outside and having a mesopore structure having a pore diameter of 2 to 20 nm. The number of mesopores changes so that the number of mesopores increases from the inside to the outside of the shell.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to hollow nanoparticles having an outer diameter of less than 1 μm, i.e., nanometer size, and a method for producing the same, and in particular to particles having an outer shell formed of silica (silicon dioxide, SiO2) and a hollow interior, the outer shell having one or more pores that connect the inner cavity to the outside. [Background technology]

[0002] Hollow nanoparticles with a silica shell have been known for some time. By dispersing them in resins or solvents, they can be used in a wide range of applications, such as transparent heat insulating films, anticorrosive paints, anti-slip coatings, light diffusing films, and gas sensors, and their shapes and properties are optimized for each application.

[0003] Patent Document 1 discloses hollow silica nanoparticles which are hollow particles made of a silica shell, have a particle diameter of 30 to 800 nm, and have no detectable pores of 2 to 20 nm. The hollow particles in Patent Document 1 are obtained by coating calcium carbonate with silica and dissolving the calcium carbonate to obtain the silica shell.

[0004] Patent Document 2 discloses a method for producing hollow particles having a particle diameter of 30 to 800 nm and a dense silica shell with no detectable pores of 2 to 20 nm. The production method disclosed in Patent Document 2 is characterized in that colloidal calcium carbonate, silicon alkoxide, and a base catalyst are mixed in an aqueous medium, silica produced by hydrolysis of the silicon alkoxide is precipitated on the surface of the colloidal calcium carbonate, and then the calcium carbonate is dissolved by acid treatment.

[0005] Patent Document 3 discloses skeleton nanoparticles having an outer diameter of 30 nm to 300 nm, a six-sided cubic frame shape that is hollow inside, and has quadrilateral holes on each face of the frame, as well as a method for producing the same.

[0006] Patent Document 4 describes a hollow nanoparticle made of a silica shell having an outer diameter in the range of 30 nm to 200 nm, having a plurality of micropores, and having a density of only the silica shell of 0.5 g / cm3 to 1.9 g / cm3. 3 The present invention discloses hollow nanoparticles composed of a low-density silica shell, characterized in that the thickness of the silica shell is 10 nm for three shells, and a method for producing the same.

[0007] Hollow nanoparticles can be used as adsorbents that selectively adsorb specific gases. For example, when mesopores of 3 to 4 nm are provided in the wall of a hollow nanoparticle that has a cavity of interconnected pores with a pore size of 50 nm or more, the presence of interconnected pores ensures the diffusion speed of gas molecules, and the gas is diffused effectively. At the same time, acetylene molecules can be selectively adsorbed in the mesopores.

[0008] Similarly, hollow nanoparticles can be used as adsorbents that selectively adsorb specific solids. For example, when 1-5 nm pores are provided in the wall of a hollow nanoparticle that has a cavity of interconnected pores with a pore diameter of 50 nm or more, gold particles can be adsorbed alone. Hollow nanoparticles that adsorb gold can be used as components of gas sensors. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2005-263550 A [Patent Document 2] JP 2006-256921 A [Patent Document 3] International Publication No. 2012 / 132757 [Patent Document 4] JP 2010-215490 A Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has an object to provide a method for producing hollow nanoparticles that are particularly suitable for use in adsorbing a specific substance. Another object of the present invention is to provide hollow nanoparticles having an optimal shape for adsorbing a specific substance. [Means for solving the problem]

[0011] The present invention relates to a method for producing hollow nanoparticles consisting of a frame-shaped silica shell. The method for producing hollow nanoparticles of the present invention includes a dispersion step of dispersing organic acid-coated calcium carbonate particles, which are obtained by coating the surfaces of dry powdered calcium carbonate particles with an organic acid, in an organic solvent, a shell formation step of mixing silicon alkoxide and a base catalyst with the dispersion liquid obtained after the dispersion step to form silica shells by a sol-gel reaction, and an acid treatment step of dissolving calcium carbonate with an acid. The production method of the present invention is characterized by not using additives such as a surfactant and a surface modifier.

[0012] The present invention relates to a hollow nanoparticle having a silica shell. The hollow nanoparticle of the present invention is a hollow nanoparticle having an outer diameter of 30 nm to 300 nm and a spherical, spheroidal, cylindrical, or frame-shaped silica shell formed entirely of six faces. The hollow nanoparticle of the present invention has one or more communicating holes that connect the internal hollow to the outside, and the pore size is 10 to 90% of the outer diameter of the silica shell. At the same time, the silica shell has one or more mesopores with a pore size of 2 to 20 nm. The hollow nanoparticle of the present invention is characterized in that the number of mesopores changes from the inside to the outside of the shell so as to increase. Effect of the Invention

[0013] The method for producing hollow nanoparticles of the present invention can produce a mesopore structure through a simplified process without using additives such as surfactants and surface modifiers.

[0014] Hollow nanoparticles having a silica shell produced without using any additives have a highly uniform silica shell surface, making it possible to adsorb substances more uniformly. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a flow chart of a method for producing hollow nanoparticles. [Diagram 2] FIG. 2 is a diagram showing a schematic diagram of the shape of a substance obtained in each step of the production method of the present invention. [Diagram 3] FIG. 3 is a diagram showing a schematic diagram of the process of forming a silica shell. [Figure 4] FIG. 4 is a photograph of a hollow nanoparticle having a silica shell according to the present invention. [Diagram 5] FIG. 5 is a partially enlarged view of the hollow nanoparticle having a silica shell of FIG. [Figure 6] FIG. 6 is a diagram showing the results of pore size distributions of hollow nanoparticles of an example and hollow nanoparticles of a comparative example estimated using density functional theory. [Figure 7] FIG. 7 is a diagram showing the results of measuring the ring structure of the hollow nanoparticle of the example by Raman spectroscopy. [Figure 8] FIG. 8 is a partially enlarged view of the results of the Raman spectroscopy shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] In this specification, "frame-like" refers to a state in which the materials that make up the structure are continuous in the form of an outer frame or framework of the structure. As mentioned above, "hollow nanoparticles" refer to particles with outer dimensions of less than 1 μm and hollow inside. "Hollow nanoparticles made of a frame-like silica shell" refers to "hollow particles whose outer frame or framework is made of silica and whose outer dimensions are specified in nanometers and are less than 1 μm."

[0017] In this specification, the term "communicating pores" without a particular size designation refers to pores with a diameter of 3 nm to 270 nm. Furthermore, the term "mesopores" without a particular size designation refers to pores with a diameter of 2 to 50 nm based on the definition set forth by the International Union of Pure and Applied Chemistry (IUPAC). Similarly, the term "micropores" without a particular size designation refers to pores with a diameter of 2 nm or less based on the definition set forth by the International Union of Pure and Applied Chemistry (IUPAC).

[0018] Hereinafter, the best mode for producing hollow nanoparticles composed of a frame-shaped silica shell and examples embodying the mode will be described with reference to the drawings. The hollow nanoparticles produced here have an outer diameter of 30 nm to 300 nm and a silica shell thickness of 3 nm to 115 nm. Figure 1 shows a flow chart of the method for producing hollow nanoparticles of this embodiment. Figure 2 shows a schematic diagram of the form of intermediate products obtained in each step of the production method.

[0019] The method for producing hollow nanoparticles of this embodiment includes a dispersion step of dispersing organic acid-coated calcium carbonate particles, which are obtained by coating the surfaces of calcium carbonate particles in a dry powder state with an organic acid, in an organic solvent, a shell formation step of mixing silicon alkoxide and a base catalyst with the dispersion liquid after the dispersion step to form a silica shell by a sol-gel reaction, and an acid treatment step of dissolving calcium carbonate with an acid. The production method of this embodiment is characterized by not using additives such as a surfactant and a surface modifier.

[0020] In order to form the silica shell, in this embodiment, dry powdered calcium carbonate particles are used as a template (mold) for the silica shell. The calcium carbonate particles have an average particle size of 8 nm to 200 nm and have a spherical, spheroidal, cylindrical, or entirely six-sided crystal structure. The surfaces of such calcium carbonate particles 1 are coated with an organic acid 2 to form organic acid-coated calcium carbonate particles 3 (step S1). FIG. 2(a) shows a schematic diagram of the organic acid-coated calcium carbonate particles 3. The coating with the organic acid 2 prevents the calcium carbonate particles 1 from agglomerating, and the calcium carbonate particles 1 become dry powdered organic acid-coated calcium carbonate particles 3.

[0021] As the organic acid 2 that coats the calcium carbonate particles 1, for example, an alkaline soap such as rosin acid or fatty acid can be used.

[0022] Next, the formed organic acid-coated calcium carbonate particles 3 are dispersed in an organic solvent (step S2). As the organic solvent, a substance that has low solubility of the organic acid and low affinity and reactivity with the calcium carbonate particles and the silicon alkoxide used in the subsequent step is used. Specifically, alcohols such as ethanol, propanol, butanol, ketones such as methyl ethyl ketone, ethers such as dioxane, and combinations of two or more of these can be used. By step S2, the organic acid 2 that coats the surface of the calcium carbonate particles 1, particularly the organic acid 2 that coats the corners and periphery, is dissolved in the organic solvent. The organic acid-coated calcium carbonate particles 3 have regions 1a where calcium carbonate is partially exposed at the corners and periphery.

[0023] Next, silicon alkoxide, distilled water, and a base catalyst are added to the organic solvent in which the organic acid-coated calcium carbonate particles 3 are dispersed, and mixed (step S3). The base catalyst hydrolyzes the silicon alkoxide, generating silica molecules (SiO2). The sol-gel reaction causes the silica shell 4 to be formed by condensation polymerization on the outside of the organic acid-coated calcium carbonate particles 3 (step S4). Figure 2(b) shows a schematic diagram of the shape of the silica shell 4 formed on the outside of the organic acid-coated calcium carbonate particles 3. Figure 3 also shows a schematic diagram of the process in which the silica shell 4 is formed by adsorbing, attaching, and accumulating silica molecules from the corners and sides of the surface of the organic acid-coated calcium carbonate particles 3 to form a silica skeleton. In Figure 3, particles indicated by circles with lighter shades indicate silica fine particles (or clusters thereof) that have been attached more recently than particles with darker shades.

[0024] As the silicon alkoxide to be added to the organic solvent, any substance capable of precipitating silica by hydrolysis can be used. Specifically, tetraethoxysilane (TEOS), trimethoxysilane, tetramethoxysilane, triethoxysilane, tripropoxysilane, tetrapropoxysilane, tributoxysilane, etc. can be used. In addition, as the base catalyst, for example, ammonia, amines, etc. can be used.

[0025] Hydroxyl groups are exposed on the surface of calcium carbonate due to the adsorption of moisture in the air. Hydroxyl groups are also exposed on the surface of precipitated silica molecules due to the adsorption of moisture in the air. The hydroxyl groups exposed on the surface of calcium carbonate and the hydroxyl groups exposed on the surface of silica molecules each have base-acid properties, so the acid-base interaction makes it easy for silica molecules to adsorb and attach to calcium carbonate. In the presence of calcium carbonate, silicon alkoxide as a silica source, and a catalyst, a silica shell 4 is formed in the area where calcium carbonate is exposed without any other special operation. On the other hand, silica does not have a chemical interaction with the organic acid 2 adsorbed on the surface of calcium carbonate particle 1. Therefore, a silica layer is not formed on the organic acid 2. As a result, a silica shell 4 is formed only on the area 1a where calcium carbonate is partially exposed of the organic acid-coated calcium carbonate particle 3, resulting in a frame.

[0026] In order to form a silica shell 4 having one or more mesopores with a pore size of 2 to 20 nm, it is necessary to optimize the temperature, reaction time, and material concentration. For example, when silica (SiO2) is formed from tetraethoxysilane (TEOS), hydrolysis and dehydration condensation occur as described below. In hydrolysis, the four alkoxy groups (OCH2CH3) at the terminals of tetraethoxysilane are decomposed into hydroxyl groups (OH). Next, the hydroxyl groups undergo dehydration condensation to form Si-O-Si bonds, resulting in silica. Here, if the reaction rate of the hydrolysis and dehydration condensation reactions is adjusted so that all four alkoxy groups of tetraethoxysilane are hydrolyzed and then all four hydrolyzed hydroxyl groups undergo dehydration condensation, the density will be 2.2 g / cm3. 3 A dense silica of at least 1000 nm is formed, and no mesopores exist in such a silica shell. On the other hand, by adjusting the temperature and pH conditions, a sparse silica shell 4 with low density and mesopores can be obtained. In addition to adjusting the temperature and pH, the reaction rate can be adjusted by optimizing the type of reaction solvent. In hydrolysis, alcohol is generated as a by-product from the alkoxy group, so if there is a sufficient reaction solvent in which alcohol is easily soluble, hydrolysis will proceed more easily. In dehydration condensation, water is generated as a by-product, so if there is a sufficient reaction solvent in which water is easily soluble, dehydration condensation will proceed more easily.

[0027] Next, the organic acid-coated calcium carbonate particles 3 with the silica shell 4 formed on the outer periphery are washed and dispersed in water, and then subjected to an acid treatment (step S5). For the acid treatment, it is preferable to adjust the hydrogen ion concentration exponent to pH 4 or less at which calcium carbonate dissolves, and for example, hydrochloric acid, oxalic acid, nitric acid, acetic acid, etc. can be used. The organic acid-coated calcium carbonate particles 3, which were the template for the silica shell 4, are dissolved by the acid and eluted from the inside of the silica shell 4. As a result, only the silica shell 4 with a hollow interior remains. The silica shell 4 is mainly a layer of silica molecules that covered the outside of the corners and peripheral regions 1a of the organic acid-coated calcium carbonate particles 3 where calcium carbonate is partially exposed, and a hollow nanoparticle with a hollow interior is formed. The morphology of the hollow nanoparticle is shown typically in FIG. 2(C).

[0028] In the method for producing hollow nanoparticles of this embodiment, the pore size of the mesopores can be adjusted by adjusting the temperature, reaction time, and material concentration in steps S1 to S5.

[0029] The method for producing hollow nanoparticles described in this embodiment can produce hollow nanoparticles that have an outer shell formed by silica, an internal cavity, and one or more holes in the shell connecting the internal cavity to the outside, without using a surfactant or surface modifier.

[0030] A photograph of hollow nanoparticles produced by the preferred production method taken with a transmission electron microscope is shown in Figure 4 as a drawing substitute photograph. Enlarged views of areas a and b in the image in Figure 4 are shown in Figures 5(a) and 5(b), respectively. Hollow nanoparticles with frame-shaped silica shells can be confirmed from the image.

[0031] Hydroxyl groups exposed on calcium carbonate and on the surface of precipitated silica molecules form a chemical structure such as Ca-O-Si because the silica molecules are easily adsorbed and attached to calcium carbonate due to acid-base interactions. Therefore, a particularly dense silica molecular frame structure is formed in the corner and peripheral area 1a where calcium carbonate is partially exposed. As a result, when silica is deposited on the calcium carbonate surface as the first layer, it forms a dense silica layer. However, as the deposition progresses, the effect of the interaction between silica molecules rather than the interaction between silica and calcium carbonate becomes greater, and furthermore, the temperature, pH, and concentration of silicon alkoxide have an effect. The fact that the silica layer is densely formed on the calcium carbonate surface and the outer silica layer is relatively coarse can be confirmed, for example, by the fact that the color of the inside of the frame structure of the silica shell 4 is dark and the contrast is clear in the area indicated by the symbol L in Figure 5(a). The difference in contrast in a transmission electron microscope is due to the difference in atoms or the difference in atomic density, and considering that the silica shell 4 is entirely made of SiO2, the difference in brightness in Figures 4 and 5 is due to the difference in atomic density. That is, a silica layer that is denser than the outside is formed on the inside of the silica shell 4 of the hollow nanoparticle of this embodiment. EXAMPLES

[0032] Hereinafter, Examples 1 to 4 of the method for producing hollow nanoparticles embodying the embodiments of the present invention and Comparative Example 1 in which hollow particles not containing mesopores were produced will be described.

[0033] Example 1 As a template, 47.91 g of calcium carbonate powder was mixed with 0.5 g of dehydroabietic acid as an organic acid to obtain organic acid-coated calcium carbonate particles 3 (step S1). The organic acid-coated calcium carbonate particles 3 were dispersed in 598.34 g of 1-propanol, an organic solvent, to partially dissolve the organic acid (step S2). Furthermore, 28.75 g of tetraethoxysilane, a silicon alkoxide, 16.87 g of 28% ammonia, a base catalyst, and 161.56 g of distilled water were added and mixed and stirred at 25°C for 90 minutes to form a silica shell (steps S3 and S4). The organic acid-coated calcium carbonate particles 3 on which the silica shell 4 was formed were washed and acid-treated with 350 mL of 3N hydrochloric acid aqueous solution to dissolve the calcium carbonate (step S5). Through the above steps, nano hollow particles made of silica shells were produced (step S6).

[0034] Example 2 In Example 2, hollow nanoparticles made of silica shell were produced using ethanol as the organic solvent. The other raw materials and production conditions were the same as in Example 1, so duplicated explanations will be omitted.

[0035] Example 3 In Example 3, the same raw materials as in Example 1 were used, and the reaction temperature in steps S3 and S4 for forming the silica shell was set to 60° C. and the reaction time was set to 60 minutes to produce hollow nanoparticles composed of a silica shell.

[0036] Example 4 In Example 4, hollow nanoparticles made of silica shell were produced using 33.54 g of tetraethoxysilane, a silicon alkoxide, and 13.50 g of 28% ammonia, a base catalyst. The other raw materials and production conditions were the same as in Example 1, so repeated explanations will be omitted.

[0037] Comparative Example 1 As a template, 0.5 g of oleic acid was added to 47.91 g of calcium carbonate powder and mixed to obtain organic acid-coated calcium carbonate particles 3 (step S1). The organic acid-coated calcium carbonate particles 3 were dispersed in 598.34 g of 1-propanol, an organic solvent, to partially dissolve the organic acid (step S2). Furthermore, 31.63 g of tetraethoxysilane, which is a silicon alkoxide, 16.87 g of 28% ammonia, which is a base catalyst, and 161.56 g of distilled water were added, and the mixture was mixed and stirred at 25°C for 90 minutes to form a silica shell (steps S3 and S4). The organic acid-coated calcium carbonate particles 3 on which the silica shell 4 was formed were washed and treated with 240 mL of 3N hydrochloric acid aqueous solution to dissolve the calcium carbonate (step S5). Through the above steps, nano hollow particles made of silica shells were produced (step S6).

[0038] Comparative Example 2 As a template, 0.5 g of oleic acid was added to 47.91 g of calcium carbonate powder and mixed to obtain organic acid-coated calcium carbonate particles 3 (step S1). The organic acid-coated calcium carbonate particles 3 were dispersed in 598.34 g of methanol, an organic solvent, to partially dissolve the organic acid (step S2). Furthermore, 31.63 g of tetraethoxysilane, which is a silicon alkoxide, 16.87 g of 28% ammonia, which is a base catalyst, and 161.56 g of distilled water were added, and the mixture was mixed and stirred at 25°C for 90 minutes to form a silica shell (steps S3 and S4). The organic acid-coated calcium carbonate particles 3 on which the silica shell 4 was formed were washed and treated with 240 mL of 3N hydrochloric acid aqueous solution to dissolve the calcium carbonate (step S5). Through the above steps, nano hollow particles made of silica shells were produced (step S6).

[0039] evaluation The relationship between the size and distribution of pore diameters in the hollow nanoparticles obtained in Example 1 and the hollow nanoparticles obtained in Comparative Example 1 was estimated using density functional theory. The estimation results for Example 1 are shown in Fig. 6(a), and the estimation results for Comparative Example 1 are shown in Fig. 6(b). In the graphs of Fig. 6(a) and Fig. 6(b), the horizontal axis represents pore diameter (unit: nm) and the vertical axis represents frequency dV / d(log D) (unit: cc / g**).

[0040] As a result of estimation using density functional theory, it was confirmed that the silica shell of the hollow nanoparticles of Example 1 has a mesopore structure with pore diameters of 2 to 10 nm, whereas the silica shell of the hollow nanoparticles of the comparative example has pores only with diameters of 10 nm to 90 nm.

[0041] Next, it will be explained that the pore size distribution of the mesopores in the hollow nanoparticles of Example 1 changes so as to become larger from the inside to the outside of the shell.

[0042] Neutron scattering was used to analyze the molecular network structure in the hollow nanoparticles of Example 1. For comparison with the hollow nanoparticles of the example, the structures of bulk glass, which is a bulk body made of amorphous silica, solid particles, which are nanoparticles made of amorphous silica, and hollow particles that have internal cavities but no communicating holes were also analyzed by neutron scattering.

[0043] It was confirmed that the nano hollow particles of Example 1 are composed of inorganic polymers linked by Si-O-Si bonds, and are amorphous silica with three-membered rings, four-membered rings, and ring structures consisting of even more Si-O-Si. It was also found that the nano hollow particles of Example 1 have a coarser silica network structure than the bulk glass, solid particles, and hollow particles used for comparison.

[0044] Furthermore, the hollow nanoparticles of Example 1 were subjected to Raman spectroscopic analysis to evaluate the structure of the silica shell. As comparative examples, Raman spectroscopic analysis was performed on solid particles with an outer diameter of 130 nm, solid particles with an outer diameter of 200 nm, and hollow particles without interconnecting holes. In addition, aluminum foil was analyzed as a control. The results are shown in FIG. 7. In the figure, the Raman spectroscopic analysis was performed on solid particles with an outer diameter of 130 nm, solid particles with an outer diameter of 200 nm, and hollow particles without interconnecting holes. -1 Peak D1 near 800 cm indicates a four-membered ring structure. -1 Peak D2 near 800 cm indicates a three-membered ring structure. -1The peak around is a peak indicating a Si-O-Si bond. As a result of the analysis, it was revealed that the solid particles have a three-membered ring structure, while the hollow particles without interconnected holes and the hollow nanoparticles of Example 1 have a four-membered ring structure. It cannot necessarily be said that a small ring structure, i.e., a three-membered ring structure, means that the particles are dense. However, considering the results of neutron scattering, it is self-evident that the solid particles having a three-membered ring structure have a dense silica network structure. In addition, there was a small but significant difference in the value of the D1 peak indicating a four-membered ring structure between the hollow particles without interconnected holes and the hollow nanoparticles of Example 1.

[0045] Fig. 8 shows a partial enlargement of the Raman spectroscopy results of Fig. 7. The D1 peak of the hollow nanoparticles of Example 1 was shifted to the lower wavenumber side compared to the D1 peak of the hollow particles without interconnected holes. This indicates that the framework structure of the hollow nanoparticles of Example 1 has a distortion in the four-membered ring structure rather than in the silica shell of the hollow particles.

[0046] From the above results of neutron scattering, Raman spectroscopy, and imaging of the nano-hollow particles by transmission electron microscope, the frame structure of the nano-hollow particles of Example 1 had a lower density and the four-membered ring structure of silica was distorted compared to the solid particles and hollow particles without interconnected holes used for comparison. Furthermore, the surface in contact with calcium carbonate on the inside of the silica shell was dense, and it became coarser toward the outside of the silica shell. From the above, it was revealed that the distribution of mesopores changed so that the number of mesopores increased from the inside to the outside of the silica shell. [Industrial Applicability]

[0047] The hollow nanoparticles of the present invention can be used not only as adsorbents but also for the separation and analysis of biomaterials. For example, when capturing exosomes that cause cancer metastasis, depression-promoting proteins, or amyloid aggregates associated with Alzheimer's disease, the body of the substance can be captured by the interconnected pores, and proteins, DNA, mRNA, etc. on the surface can be firmly captured by fitting them into the mesopores. Furthermore, the hollow nanoparticles can be applied to the separation and analysis of substances captured by the interconnected pores and substances captured by the mesopores. [Explanation of symbols]

[0048] 1. Calcium particles 2 Organic acids 3. Organic acid-coated calcium carbonate particles 4. Silica Shell

Claims

1. A method for producing hollow nanoparticles composed of a frame-shaped silica shell, comprising the steps of: a dispersing step of dispersing organic acid-coated calcium carbonate particles obtained by coating the surfaces of dry powdered calcium carbonate particles with an organic acid in an organic solvent; a shell formation step of mixing a silicon alkoxide and a base catalyst with the dispersion liquid after the dispersion step to form a silica shell by a sol-gel reaction; an acid treatment step of dissolving calcium carbonate with an acid; Equipped with A method for producing hollow nanoparticles, characterized in that no additives such as surfactants and surface modifiers are used.

2. A hollow nanoparticle having an outer diameter of 30 nm to 300 nm and made of a silica shell in the shape of a sphere, spheroid, cylinder, or a frame having six sides in its entirety, the silica shell has one or more communicating holes that communicate the internal hollow with the outside, the communicating holes having a pore size of 10 to 90% of the pore size of the silica shell; and the silica shell has one or more mesopores having a pore size of 2 to 20 nm; A hollow nanoparticle, characterized in that the number of mesopores changes from the inside to the outside of the shell so that it becomes more numerous.

Citation Information

Patent Citations

  • High dispersion silica NANO hollow particle and its producing method

    JP2005263550A

  • Manufacturing method of silica hollow particle

    JP2006256921A

  • Hollow nanoparticle composed of low density silica shell, and method for producing the same

    JP2010215490A

  • Skeleton nanoparticles and method for producing same

    WO2012132757A1